2021
DOI: 10.53802/hikmah.v18i1.101
|View full text |Cite
|
Sign up to set email alerts
|

Pembelajaran Konvensional dan Kritis Kreatif dalam Perspektif Pendidikan Islam

Abstract: This research aims to determine the perspective of Islamic education about conventional learning and critical creative learning. This research is library research and data collection uses documentation method. The data analysis uses a comparative technique, namely researching the philosophical foundations of conventional learning and critical-creative learning and looking at the two learning concepts using the perspective of Islamic education. Islamic education is the process of changing individual behavior in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 17 publications
0
16
0
2
Order By: Relevance
“…In comparison to traditional models of education, the teaching and learning process is highly monitored and verbal (Fahrudin et al, 2021). A student will accept only what an educator offers.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to traditional models of education, the teaching and learning process is highly monitored and verbal (Fahrudin et al, 2021). A student will accept only what an educator offers.…”
Section: Resultsmentioning
confidence: 99%
“…Questioning serves to lure students into being actively involved in ongoing learning. Also, it aims to lure students who previously needed to pay more attention to learning to change to paying attention to learning 19 . In class, the teacher presents the material discussed in the meeting with students.…”
Section: B Askingmentioning
confidence: 99%
“…That this study found that lecture-based teaching model did not significantly improve students' learning outcome is consistent with the research conducted by Peranginangin et al (2020), which states that conventional methods cannot enhance students' learning outcomes. The conventional teaching models that focus on the teacher, such as lecture-based teaching model (Fahrudin et al, 2021) makes students uninterested in the learning process. This is indicated by their lazy attitude towards attending classes, lack of focus during teacher explanations, falling asleep during lessons, and neglecting assignments.…”
Section: Table 3 Paired Sampe T-testmentioning
confidence: 99%
“…& Fauzi., 2018). The conventional teaching model is often used by teachers (Fahrudin et al, 2021). Conventional teaching, primarily lecturebased teaching model, can lead to student boredom, as evidenced by attitudes such as laziness, lethargy, inattentiveness to the teacher's explanations, and reluctance to complete assignments (Novialistra et al, 2022).…”
Section: Introductionmentioning
confidence: 99%